Uji Aktivitas Isoflavon Tempe terhadap Penghambatan Enzim α-Glukosidase dan Pengaruhnya pada Tikus Hiperglikemik - I NYOMAN SUARSANA (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Isoflavone is a bioactive compound found in fermented soy bean or tempe, and found to have beneficial effect on human health. The objectives of this research were to assay the activity of tempe isoliavone in inhibiting the α-glucosidase enzyme in vitro and to determine the dosage of antihyperglycemic activity of isoflavone tempe. inhibitory effects of tempe isoflavone on α-glucosidase enzyme was tested by spectrofotometry method while in vivo evaluation are conducted using rats under hyperglycemic condition. A total of thirty five male Spraque Dawley rats, which is two months old were used in this study. The rats were divided into seven groups: (1) negative control group; (2) positive hyperglycemic group; (3-6) positive hyperglycemic group and treated with tempe isoflavone with dosages of 100, 200, 300, and 400 mg/kg body weight (bw); and (7) positive hyperglycemic group treated with acarbose dosage of 4,5 mg/kg bw. Blood glucose level was evaluated every 0, 30, 60, 120, 180, and 240 minutes following treatment using Blood Blucose Test Meter GlucoDr. The result showed that the inhibitory effect of tempe isoflavone on α-glucosidase enzyme was 11.89%, with IC50 1.4 mg, and this mechanisms are caused by daidzein and genistein. lsoflavone of tempe with dose of 400 mg/kg bw showed an antihyperglycemie effect.